Functional Literacy in the System of Adult Education - Olena Vasylenko (Horyzonty Wychowania, 2023)
RESEARCH OBJECTIVE: The scientific aim of the article is to improve understanding of func- tional literacy (illiteracy) phenomenon and its role in adult learning system, pedagogical and socio-economic approaches to this concept.